1960
DOI: 10.1002/j.1537-2197.1960.tb07123.x
|View full text |Cite
|
Sign up to set email alerts
|

Shoot Histogenesis: Subapical Meristematic Activity in a Caulescent Plant and the Action of Gibberellic Acid and Amo‐1618

Abstract: Sachs, R. M., A. Lang, C. F. Bretz and Joan Roach. (U. California, Los Angeles.) Shoot histogenesis: subapical meristematic activity in a caulescent plant and the action of gibberellic acid and Amo—1618. Amer. Jour. Bot. 47(4): 260—266. Illus. 1960.–Studies on gibbereilininduced stem formation in rosette plants (Sachs et al., 1959) have shown that a zone of intensive meristematic activity, arising below the existing apical meristem, is almost solely responsible for stem histogenesis, i.e., the formation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
28
0
3

Year Published

1961
1961
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 12 publications
7
28
0
3
Order By: Relevance
“…When injected into the central corpus, LYCH distributed in a rectangular area without entering the RM (data not shown). Together, these experiments provided support for the classic notion that the RM is a morphogenetic unit in its own right (Sachs et al, 1960;Esau, 1977).…”
Section: Pinpointing the Rm In The Apex Of Poplarsupporting
confidence: 55%
See 1 more Smart Citation
“…When injected into the central corpus, LYCH distributed in a rectangular area without entering the RM (data not shown). Together, these experiments provided support for the classic notion that the RM is a morphogenetic unit in its own right (Sachs et al, 1960;Esau, 1977).…”
Section: Pinpointing the Rm In The Apex Of Poplarsupporting
confidence: 55%
“…Cells in the corpus of the SAM divide more or less randomly, following space-filling requirements, while those recruited by the subtending RM start to divide periclinally to produce the ribs of the RZ. Following these established criteria (Sachs et al, 1960;Esau, 1977), the poplar SAM includes a two-cell layered tunica and a corpus of five to six cell layers ( Figures 7A and 7B). Immediately adjacent to the corpus is the RM composed of about two to four cell layers ( Figure 7B).…”
Section: Pinpointing the Rm In The Apex Of Poplarmentioning
confidence: 99%
“…Growth retardants often exert their effects on plants via their inhibitory effect on endogenous GA biosynthesis, which is involved in cell elongation (Cathey, 1964;Masuda et al, 1970;Yamada, 1976). For example, the retardant AMO-1618 inhibits cell elongation by disrupting GA biosynthesis in the stem of chrysanthemum (Sachs et al, 1960). As SADH also inhibits endogenous GA synthesis (Yamada, 1976), it is considered that impaired cell enlargement in fruits treated with SADH is due to the inhibition of endogenous GA biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…GA3 application to cotyledons also reverses inhibition of flowering, but the material is probably rapidly translocated to the apex. B) The growth retardant Amo-1618 completely inhibits subapical meristematic activity in Chrysanthemum (9). Anatomical observations in Pharbitis showed that CCC strongly reduces cell number in the first internode which is just beginning to expand at the time of induction.…”
Section: Discussionmentioning
confidence: 99%